INDIVIDUALIZED TRAINING - THE BASIC METHOD IN THE PHYSICAL TRAINING OF FOOTBALL PLAYERS - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
The individualization of the training is done by modeling, which appears as a principle, but also as a method. It aims to maintain the sporty form through a fair dosage in which work with different volume and intensity is usually adapted to maximum efforts. The individualization of the training helps us by the fact that, knowing how to dose the individual effort, we can apply a greater number of technical - tactical exercises, which contributes to the progress in this respect.